Faktor yang Mempengaruhi Struktur Gaji Berbasis Kinerja Pada Perguruan Tinggi Swasta - S.K, Purwanto; Sari, Endah Murtiana; Rismawati, Rismawati (Education : Jurnal Sosial Humaniora dan Pendidikan, 2025)
The development of Private Higher Education Institutions (Private HE) in Indonesia is very massive, with more than 2500 Private HE institutions operating in the form of Universities, Colleges, Academies, polytechnics, and Institutes in Indonesia. This challenge highlights the importance of effective management in maintaining the continuity of operations run by Private HE. Salary is a crucial element that must be arranged systematically and fairly to maintain long-term employee retention for sustainable Private HE. This study aims to determine the factors that influence the preparation of performance-based salaries in Private HE. Using qualitative methods, this study will conduct a systematic literature review (SLR) from previous literature from national and international research, such as journals and books, to group important factors considered to influence the preparation of salaries in Private HE. This study provides benefits to researchers, academics, and Private HE managers in maintaining employee retention through the preparation of performance-based salaries. This study is a preliminary finding that can be studied further to produce broader research to develop performance-based salaries in Indonesian private HE.